Pemberdayaan Karang Taruna Desa dalam Pengembangan dan Pengelolaan Wisata Alam - Afandi, Khoirul; Fitriawan, Fuad; Budiwan, Jauhan (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This program aims to improve the quality of community empowerment in the Development and Management of Tourism Villages in Sukorejo Village, Sukorejo District, Ponorogo Regency, East Java Province. One of the strategies implemented is to optimize the human resources of youth organizations to be more astute in exploiting local tourism potential. The main target of this activity is Karang Taruna Bolo Sewu and all elements of society in Sukorejo Village. Apart from that, students also collaborate with the village government by holding digital seminars aimed at promoting local tourism through digital media. The Bolosewu Youth Organization's activity method in Sukorejo Village in the KPM program with the theme